The Influence of a Damaged Concrete Cover on the Behavior of a Simply-Supported Beam - Khalid K. Shadhan; Bilal Ismaeel Abd Al-Zahra; Muhammad Jawad Kadhim (Civil Engineering Journal, 2023)
The concrete cover is a part of the concrete that provides the required protection for the reinforcing steel within the required element from external effects. This concrete cover can be damaged for an assortment of reasons, one of which is environmental factors. As a result, this research focused on the effect of worn concrete covering on the structural response of beams. Moreover, the possibility of repairing or replacing this concrete cover with a cement material was done by testing seven beams with the exact dimensions (2700 mm long, 250 mm deep, and 140 mm wide). The first specimen was a control specimen, while in the remaining specimens, a part of the concrete cover was removed in the midspan region with a length of 600 mm and in different formats. The part below the neutral axis (tension zone) was removed in the first two specimens. The part above the neutral axis (the compression zone) was removed in the second two specimens. The whole cover was removed within the specified distance for the other two specimens. In one out of every two of these six specimens, the removed concrete cover was replaced with cementitious material. A flexural test was performed for all specimens, and the conclusion was reached that damaging or removing the concrete cover from the tensile region (below the neutral axis) is less harmful than from the compression region since the beam is often designed as a cracked section. Also, removing the concrete cover from the compression region gives cracks a greater width than removing the concrete cover from the tension region at the same loading level. In the case of replacing the concrete cover with a cementitious one, if the replacement is in the compression zone, it will result in cracks when loading with a width greater than that of the rest of the cases. For specimens that removed their concrete covers from the tension zone, compression zone, and the whole section, the failure loads decreased by 39%, 20%, and 23%, respectively, concerning the control beam. In contrast, all these specimens were repaired with cementitious materials, with an ultimate load capacity approximately equal to the control beams. From these results, any damaged concrete cover for beams in any zone with cementitious materials having high strength and a good bond with old concrete sections can be repaired.Â Doi: 10.28991/CEJ-2023-09-07-09 Full Text: PDF